2016
DOI: 10.1039/c6fo00942e
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioaccessibility and functional properties of polyphenols from pomegranate peels and pomegranate peels-enriched cookies

Abstract: Obesity is an urgent social problem and new functional foods providing polyphenols and dietary fibers (DF) may be promising tools to modulate oxidative stress, inflammation and energy homeostasis. Pomegranate peels (PPe) are an agro-industrial by-product containing polyphenols such as ellagitannins (ETs), gallic acid (GA), ellagic acid (EA) and its derivatives (EAs), as well as DF. In this study, PPe enriched cookies (PPeC) were developed, and the bioaccessibility as well as the ability of their polyphenols to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Various agri-food by-products rich in polyphenols, including pomegranate, mango, pigeon pea, and apple peels, have been mixed to the dough to prepare bakery products with functional properties. Some researchers reported that the supplementation of polyphenols in bakery foods could decrease starch digestibility and reduce the postprandial glucose levels in the serum, and is thus considered as alternatives to pharmaceutical interventions for the treatment of type II diabetes [25,26,27,28]. In this work, the addition of fermented OP to durum wheat flour led to a significant enrichment of polyphenol compounds.…”
Section: Resultsmentioning
confidence: 90%
“…Various agri-food by-products rich in polyphenols, including pomegranate, mango, pigeon pea, and apple peels, have been mixed to the dough to prepare bakery products with functional properties. Some researchers reported that the supplementation of polyphenols in bakery foods could decrease starch digestibility and reduce the postprandial glucose levels in the serum, and is thus considered as alternatives to pharmaceutical interventions for the treatment of type II diabetes [25,26,27,28]. In this work, the addition of fermented OP to durum wheat flour led to a significant enrichment of polyphenol compounds.…”
Section: Resultsmentioning
confidence: 90%
“…ETs ( α and β anomers of punicalin, punicalagin and pedunculagin), GA, EA and EAs (EA hexoside, EA pentoside, EA deoxyhexoside) were identified by liquid chromatography/tandem mass spectrometry (LC/MS/MS) and quantified by HPLC with diode array detection (HPLC‐DAD) according to Colantuono et al . Each sample was properly diluted in water/methanol (50:50 v/v) acidified with 5 mL L −1 formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 3.8 mL of bitartrate buffer solution in 120 mL L −1 ethanol (pH 3.6) was mixed with 100 µL of sample. The absorbance ( A ) at 520 nm was measured and the final value was multiplied by 20. The different forms of anthocyanins were expressed in absorbance units as copigmented anthocyanins0.25em()CPA=AacetA20 monomeric anthocyanins0.25em()MA=A20ASO2 polymeric anthocyanins0.25em()PA=ASO2 total anthocyanins=Aacet …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides tea ( Camellia sinensis ), fruits that have been shown to contain high levels of gallic acid or its derivative compounds include avocado, ellagitannin-enriched polyphenolic extract, Eugenia dysenterica DC., freeze-dried jaboticaba peel, grape powder, herbal mixture, Limonium spp . (Plumbaginaceae), Mangifera indica L., mango, mulberry water, Nelumbo nucifera leaf, Norton grape pomace, number ten supplement, Ocimum basilicum , pineapple, pomegranate peels, Psidium guajava L., Pedro Sato, Paluma and Século XXI, Pu-erh tea, Punica granatum , Ribes nigrum L , Rubus suavissimus , and Terminalia bellirica [11,15,19,98,99,102,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,142,143,145].…”
Section: Evidence On the Anti-obesity Properties Of Tea And Fruitsmentioning
confidence: 99%